Dampak Peran Ayah dalam Pendidikan Agama Anak di Menganti Kedung Jepara - Avrilya Safitri, Della; Rohman, Fathur (Paedagogie: Jurnal Pendidikan dan Studi Islam, 2026)
This study examines the lack of father's role in children's religious education in Menganti Village, Kedung District, Jepara Regency. Employing a qualitative approach with case study design, the research involved 30 participants consisting of fathers, mothers, Islamic education teachers, religious leaders, and children. Data was collected through in-depth interviews, participatory observation, and documentation, then analyzed using Miles and Huberman's interactive analysis model. The results show that the reality of father's role in children's religious education remains very minimal, with 80% of fathers delegating responsibility to mothers and formal educational institutions. The lack of father's role is caused by five main factors: time constraints due to economic demands, misconceptions about role division, lack of knowledge and skills, misguided patriarchal cultural influences, and challenges in digital era. The impacts include the lack of understanding in Islamic teachings, low consistency in worship practices, absence of religious role models, and emergence of behavioral problems and religious identity crisis. This study emphasizes the importance of father's active involvement in religious education as a leadership mandate that cannot be fully delegated to others.